An agent-based model of household energy consumption. (1st January 2020) - Tian, Shanjun; Chang, Shiyan
Abstract: How to increase clean energy utilization is a key issue in household energy consumption analysis aimed at alleviating air pollution and improving the health of residents. Clean energy substitution is a complex decision process between related stakeholders, and is affected by a combination of factors such as geographical location and household income. To evaluate the potential of clean energy promotion to contribute to better policy decisions and measures, an agent-based household energy consumption model is established to capture the group habits of different stakeholders and the impact mechanism of critical influential factors. Multi-layered structures including various types of households and energy consumption devices are modeled. The experimental results of several scenario analyses show that increased income, improved technology and subsidies from local governments can influence clean energy substitution in the household in various ways. These findings provide a better understanding of the energy cleaning process and decision-making support for governments.